Reproductive biology and condition factor of the African catfish, Clarias gariepinus (Burchell 1822) in Lake Koka, Ethiopia - Alemayehu Wubie; Adamneh Dagne; Gashaw Tesfaye; Genanaw Tesfaye; Dawit Adisu Tadese (Journal of Fisheries, 2023)
The study was conducted to investigate the breeding season, sex ratio, size at maturation, fecundity and condition factor of African catfish Clarias gariepinus in Lake Koka. A total of 754 fish specimens were collected from October 2020 to August 2021. Total length and weight were measured and sexes were identified and gonad maturity levels were recorded. The sex ratio of African catfish in different size classes was similar to that of a hypothetical 1:1 ratio. The length at first maturity (L50) was 51.8 cm in total length. The mean Fulton’s condition factor of female African catfish ranged from 0.65 ± 0.05 – 0.71 ± 0.14, while the males ranged from 0.62 ± 0.04 – 0.7 ± 0.11. The Fulton’s condition factor was significantly higher in August for females than in the rest of the sampling months. The highest ripe gonads were recorded in the rainy season and the lowest was in the dry season, with the percentage of ripe gonads being 27.5%, while the males showed similarly extended maturity patterns among seasons. Fisheries management for African catfish should therefore take into account the estimated L50 value and the main breeding season to sustain the fishery and benefits the fishermen.